microRNA‐16‐5p‐containing exosomes derived from bone marrow‐derived mesenchymal stem cells inhibit proliferation, migration, and invasion, while promoting apoptosis of colorectal cancer cells by downregulating ITGA2 - Xu, Yan; Shen, Liangfang; Li, Fujun; Yang, Junwen; Wan, Xiaoping; Ouyang, Miao (Journal of cellular physiology, 2019)
Colorectal cancer (CRC) is a form of cancer developing from either the colon or rectum. Nowadays, research supports the functionality of exosome expressing microRNAs (miRNAs) as potential biomarker for various cancers including CRC. This study was performed with the intent of investigating the roles of both bone marrow‐derived mesenchymal stem cells (BMSCs) and exosomal miR‐16‐5p in CRC by regulating integrin α2 (ITGA2). A microarray‐based analysis was conducted to screen the CRC‐associated differentially expressed genes (DEGs) as well as potential regulatory miRNAs. Next, the role of miR‐16‐5p in terms of its progression in association with CRC was determined. Subsequently, CRC cells were exposed to exosomes secreted by BMSCs transfected with miR‐16‐5p, isolated and cocultured with CRC cells in an attempt to identify the role of exosomes. Effects of BMSCs‐derived exosomes overexpressing miR‐16‐5p on biological functions of CRC cells and tumorigenicity were all subsequently detected. Effects of miR‐16‐5p treated with CRC cells in regard to CRC in vivo were also measured. ITGA2 was overexpressed, while miR‐16‐5p was poorly expressed in CRC cells and miR‐16‐5p targeted ITGA2. The in vitro experiments revealed that the BMSCs‐derived exosomes overexpressing miR‐16‐5p inhibited proliferation, migration, and invasion, while simultaneously stimulating the apoptosis of the CRC cells via downregulation of ITGA2. Furthermore, the results of in vivo experiments confirmed that the BMSCs‐derived exosomes overexpressing miR‐16‐5p repressed the tumor growth of CRC. Collectively, BMSCs‐derived exosomes overexpressing miR‐16‐5p restricted the progression of CRC by downregulating ITGA2. Collectively, bone marrow‐derived mesenchymal stem cells (BMSCs)‐derived exosomes overexpressing miR‐16‐5p restricted the progression of colorectal cancer (CRC) by downregulating integrin α2 (ITGA2).